Pengaruh Pemberian Sekam, Bokashi Dan Trikopukan Terhadap Pertumbuhan Dan Hasil Tanaman Okra (Abelmoschus esculentus L. Moench) - Jurkani Jurkani; Fadly Hairannoor Yusran; Antar Sofyan (Agroekotek View, 2019)
This research aims to determine which treatment has significant effect using organic materials such as Husk, Bokashi and Trikopukan, so that later the research results can provide information to farmers to apply to the field and other students to make reference material for further research. The formulation of the problem is whether Three are differences in effect of the application of organic matter to growth and result of the okra and on which organic ingredients have the best or real influence. The research was conducted on at the Land Owned by  Wahana Kalimantan Institute, North Loktabat, Banjarbaru. The time for conducting this study lasted three months, starting from September to November 2017. In this study using a randomized block design method consisting of five treatments including controls and four replications namely T0: control, T1: 1.5 kg husk, T2: 1, 5 kg of bokashi, T3: 1.5 kg of trichopukan and T4 of 1.5 kg composite. The research results obtained after the observation were that organic matter with a dose of 10 t ha-1 could increase the growth rate and yield of okra plants, especially organic matter fermented with trichoderma microorganisms able to show a very significant effect on all observation variables, while the best treatment was indicated by treatment trichopukan.